2010
DOI: 10.1128/iai.00703-09
|View full text |Cite
|
Sign up to set email alerts
|

Protection against LethalNeospora caninumInfection in Mice Induced by Heterologous Vaccination with amic1 mic3KnockoutToxoplasma gondiiStrain

Abstract: Neospora caninum and Toxoplasma gondii are closely related, obligate intracellular parasites infecting a wide range of vertebrate hosts and causing abortion and neonatal morbidity and mortality. Several lines of evidence suggest that cross immunity between these two pathogens could be exploited in the design of strategies for heterologous vaccination. We assessed the ability of an attenuated strain of T. gondii ("mic1-3KO strain") conferring strong protection against chronic and congenital toxoplasmosis to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 42 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Despite considerable efforts, there is currently no effective vaccine against neosporosis on the market. Experimental live vaccines comprised of attenuated N. caninum strains exhibited promising efficacy in pregnant mice and cattle [27][28][29][30][31], while classical subunit vaccines composed of recombinant antigens showed rather limited efficacy [2,32,33]. However, the pharmaceutical industry appears reluctant to invest in a product with a limited shelf life, high production costs, and uncertainty about development of virulence [34].…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable efforts, there is currently no effective vaccine against neosporosis on the market. Experimental live vaccines comprised of attenuated N. caninum strains exhibited promising efficacy in pregnant mice and cattle [27][28][29][30][31], while classical subunit vaccines composed of recombinant antigens showed rather limited efficacy [2,32,33]. However, the pharmaceutical industry appears reluctant to invest in a product with a limited shelf life, high production costs, and uncertainty about development of virulence [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, this important stage has scarcely been investigated as an oral infectious material because the tachyzoite is sensitive to gastric juice. It has been reported that tachyzoites can infect cats and mice via the oral route [ 9 , 34 ]. In our previous studies, we have successfully established that tachyzoites infected a mouse model via the oral route [ 45 , 47 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…While vaccination with T. gondii failed to prevent fetal transmission after N. caninum challenge in sheep [ 27 ], heterologuous vaccination using a T. gondii Mic1-Mic3-KO strain conferred protection against lethal challenge of N. caninum in mice by both oral and intraperitoneal vaccination routes with 80% and 70% survival rates, respectively. Interestingly, immunization of the mice with the Nc-1 strain conferred the same level of protection when administered orally (70% of survivors), whereas none of the mice that were injected intraperitoneally survived [ 65 ]. However, the genotypes of all these parasite populations are not well defined, and the risks associated with using live parasite populations as live vaccines in cattle may be significant, as there is the concern that these organisms might reverse to a disease-causing phenotype.…”
Section: Vaccines Against Neosporosismentioning
confidence: 99%